Algorithmic Approaches in Diagnostic Decision Support for Combined Use of Speckle-Tracking Echocardiography and Coronary Angiography in Patients with Coronary Artery Disease - E. A. Nastenko; S. V. Potashev; O. V. Rybakova; Yu. V. Didyk (Ukrainian Journal of Cardiovascular Surgery, 2021)
Background. Improving methods of coronary artery disease (CAD) diagnosis involves determining the most informative and less expensive methods. Speckle tracking echocardiography (STE) is now widely used for early myocardial ischemia diagnosis, allowing better verification of ambivalent results of coronary angiography (CAG).The aim. To develop algorithmic approaches to early CAD diagnosis through the combined use of STE and CAG in order to increase accuracy and reduce the cost of diagnosis and treatment of CAD.Methods. We examined 568 patients (425 [74.8%] men and 143 [25.2%] women) aged 62.3±8.9 years admitted to our center for diagnosis verification and establishing indications for coronary interventions. All the patients underwent CAG directly before or after STE.Results. Through both methods no pathology was detected in 5.2% of men and 16.8% of women. In 2.6% of men and 4.2% of women, STE found no regional strain disorders in the absence of significant alterations in coronary arteries (CA) according to CAG. Such false-positive STE results may witness of: 1) insignificant myocardial ischemia due to congenital distal coronary branches tortuosity or intramural (I/M) CA course, as well as myocardial ischemia due to microcirculation disorders not diagnosed by CAG; 2) non-coronary myocardial dysfunction. In 1.2% of men and 4.2% of women, CAG found significant or insignificant (up to 50–70%) atherosclerotic stenotic lesions in the absence of data suggestive of myocardial ischemia by longitudinal strain “drop” during STE. Such false-negative STE results may witness of high coronary reserve due to advanced collateral circulation in viable myocardium in ischemic coronary area. Myocardial ischemia according to both coronary beds visualization through CAG, as well as according to characteristic regional strain decrease revealed by STE, was found in 91.1% men and 74.8% women, witnessing of high correlation of the results obtained through both methods. Such results show coincidence of signs of hemodynamically significant CA stenoses according to both methods, including I/M CA segments course.Conclusions. Combination of CAG and STE in patients with CAD allows better determination of CA lesions hemodynamic significance, including I/M CA segments course, and to use STE as a non-invasive imaging technique in CAD, including pharmacological stress test. Combined CAG and STE use with integrated analysis thereof allows identification of coronary circulatory disorders that could not be detected separately, helping to increase diagnostic accuracy and to improve cost-effectiveness of diagnosis and treatment.